Functional Nanocomplexes with Vascular Endothelial Growth Factor A/C Isoforms Improve Collateral Circulation and Cardiac Function. Issue 4 (26th December 2019) - Qiao, Bokang; Nie, Jing‐Jun; Shao, Yihui; Li, Yulin; Zhang, Congcong; Hao, Wenjing; Li, Sijin; Chen, Dafu; Yu, Bingran; Li, Hui‐Hua; Xu, Fu‐Jian; Du, Jie
Abstract: Protein‐based therapies are potential treatments for cancer, immunological, and cardiovascular diseases. However, effective delivery systems are needed because of their instability, immunogenicity, and so on. Crosslinked negatively charged heparin polysaccharide nanoparticle (HepNP) is proposed for protein delivery. HepNP can efficiently condense vascular endothelial growth factor (VEGF) because of the unique electronegative sulfonic acid and carboxyl domain of heparin. HepNP is then assembled with VEGF‐C (Hep@VEGF‐C) or VEGF‐A (Hep@VEGF‐A) protein for the therapy of myocardial infarction (MI) via intravenous (iv) injection. Hep@VEGF‐A‐mediated improvement of cardiac function by promoting angiogenesis is limited because of elevated vascular permeability, while Hep@VEGF‐C effectively promotes lymphangiogenesis and reduces edema. On this basis, a graded delivery of VEGF‐C (0.5–1 h post‐MI) and VEGF‐A (5 d post‐MI) using HepNP is developed. At the dose ratio of 3:1 (Hep@VEGF‐C vs Hep@VEGF‐A), Hep@VEGF functional complexes substantially reduce the scar formation (≈−39%; p < 0.05) and improve cardiac function (≈+74%; p < 0.05). Such a HepNP delivery system provides a simple and effective therapeutic strategy for cardiovascular diseases by delivering functional proteins. Because of the unique binding ability of heparin with cytokines and growth factors, HepNP also has considerable application prospects in protein therapy for other serious diseases. Abstract : A crosslinked negatively charged heparin polysaccharide‐based nanoparticle named HepNP is successfully proposed for the coordinated delivery of vascular endothelial growth factor (VEGF)‐C and VEGF‐A proteins for myocardial infarction therapy by improving the collateral circulation.